Visualization of electrical field of electrode using voltage-controlled fluorescence release. (1st August 2016) - Jia, Wenyan; Wu, Jiamin; Gao, Di; Wang, Hao; Sun, Mingui
Abstract: In this study we propose an approach to directly visualize electrical current distribution at the electrode–electrolyte interface of a biopotential electrode. High-speed fluorescent microscopic images are acquired when an electric potential is applied across the interface to trigger the release of fluorescent material from the surface of the electrode. These images are analyzed computationally to obtain the distribution of the electric field from the fluorescent intensity of each pixel. Our approach allows direct observation of microscopic electrical current distribution around the electrode. Experiments are conducted to validate the feasibility of the fluorescent imaging method. Highlights: We developed a method to image electrical current distribution of electrode. We coated electrode with voltage-controlled fluorescent tracer. Current distribution was observed by high-speed imaging after tracer release. A computational method was derived to calculate the distribution from acquired images.